EFEKTIVITAS IMPLEMENTASI KEBIJAKAN PENATAAN LEMBAGA KEMASYARAKATAN RUKUN TETANGGA DAN RUKUN WARGA DI KABUPATEN BOGOR PROVINSI JAWA BARAT - Hyronimus Rowa; Florianus Aser (Jurnal Ilmiah Wahana Bhakti Praja, 2019)
Abstract The existence of the RT and RW as a Society Institution intended to accelerate the realization of Government along with the villagers and the village self-sufficient, progressive, independent and prosperous Republic Unitary State bond in Indonesia. Through such positions, RT and RW as actors of intregration the local self government and a self governing community thus generating socially governing community. But in the context of its implementation, the content and purpose of policy is failured and is bad execution. The effectiveness of the procedural and substantial effectiveness are in the category of unsuccessfull implementation and non-implementation. Implementation of the policy of RT and RW Setup as a socially community institution more purely "symbolic implementation". Keywords: unsuccessfull, socially governing community, symbolic implementation